A new species of Tanacetipathes from Brazil, with a redescription of the type species T. tanacetum (Pourtales) (Cnidaria, Anthozoa, Antipatharia) - Pérez, C. D.; Costa, D. L.; Opresko, D. M. (Zootaxa, 2005)
The type species of Tanacetipathes Opresko, 2001 is Antipathes tanacetum Pourtalès, 1880. Pourtalès did not designate a holotype for A. tanacetum, nor did he indicate which form he thought was the most “typical” of the species. Because of the similarities of some of the syntypes with other nominal species, it is necessary to select a lectotype from one of the two groups with predominantly uniserial pinnulation. A specimen with short curved primary pinnules was chosen because it has a very distinctive pinnulation pattern that has been previously associated with Tanacetipathes tanacetum. With a lectotype of T. tanacetum designated, potential new species of Tanacetipathes can now be evaluated and compared directly with the type species. This is the case for T. paula n. sp., which is described here from the littoral of Archipelago of Saint Peter and Saint Paul (Brazil). This species has a corallum pseudo-dichotomously branched, with primary pinnules arranged in four rows and in alternating biserial groups of two pinnules each. The primary pinnules are up to 1.9 cm in length. The secondary pinnules usually occur bilaterally, on both sides of the primary pinnules, and often in subopposite pairs, especially near the base of the primary pinnules. There are usually 3-9 secondary pinnules per lateral primary pinnules. The anterior primary pinnules always with only two secondary pinnules arranged in subopposite pair nearer the base of primary. The axial spines are relatively large, conical, acute and slightly papillose; the polypar spines up to 0.25 mm tall and abpolypar spines up to 0.17 mm. Polyps are not present on the type specimen.